A Hierarchical Multiple Regression Approach on Determining the Effect of Psychological Capital on Entrepreneurial Intention amongst Prospective University Graduates in South Africa - Clifford Kendrick Hlatywayo; Chioneso Show Marange; Willie Tafadzwa Chinyamurindi (Journal of Economics and Behavioral Studies, 2017)
The goal of the study is to identify the contribution of psychological capital in the prediction of entrepreneurial intention using the Theory of Planned Behaviour (TPB) as a theoretical lens. South Africa needs young entrepreneurs, not job seekers. However, in order to adapt, graduates must rely on psychological resources to succeed in their entrepreneurial ventures and pursuits. Using the TPB and Psychological capital (Psycap), the researchers explored the influence of planned behaviour and Pyscap on entrepreneurial intention of 270 final year students in the Management and Commerce faculty at a selected university in the Eastern Cape Province of South Africa. A structured questionnaire was used to collect data as the researchers opted for a survey design. Results of hierarchical multiple regression modelling showed that entrepreneurial intentions is positively influenced by perceived behavioural control (Î²1 = 0.367; p = <0.0001) attitudes towards becoming an entrepreneur (Î²2 = 0.316; p = <0.0001) and resilience (Î²3 = 0.130; p = 0.009). The resultant model revealed that resilience (Î”R2 = 0.016; R2 = 0.392; df = 266; p = 0.009) was the only significant psychological capital construct that added unique variance in predicting entrepreneurial intention above and beyond, which is predicted by the theory of planned behavior variables among the prospective graduates. Findings of the study are helpful to policy makers as they try to optimise strategies for entrepreneurial success in the South African context and the developing world.